SIRT6 Suppresses Cancer Stem-like Capacity in Tumors with PI3K Activation Independently of Its Deacetylase Activity - Ioris, Rafael M.; Galié, Mirco; Ramadori, Giorgio; Anderson, Jason G.; Charollais, Anne; Konstantinidou, Georgia; Brenachot, Xavier; Aras, Ebru; Goga, Algera; Ceglia, Nicholas; Sebastián, Carlos; Martinvalet, Denis; et al. (Cell reports (Cambridge), 2017)
Cancer stem cells (CSCs) have high tumorigenic capacity. Here, we show that stem-like traits of specific human cancer cells are reduced by overexpression of the histone deacetylase sirtuin 6 (SIRT6). SIRT6-sensitive cancer cells bear mutations that activate phosphatidylinositol-3-kinase (PI3K) signaling, and overexpression of SIRT6 reduces growth, progression, and grade of breast cancer in a mouse model with PI3K activation. Tumor metabolomic and transcriptomic analyses reveal that SIRT6 overexpression dampens PI3K signaling and stem-like characteristics and causes metabolic rearrangements in this cancer model. Ablation of a PI3K activating mutation in otherwise isogenic cancer cells is sufficient to convert SIRT6-sensitive into SIRT6-insensitive cells. SIRT6 overexpression suppresses PI3K signaling at the transcriptional level and antagonizes tumor sphere formation independent of its histone deacetylase activity. Our data identify SIRT6 as a putative molecular target that hinders stemness of tumors with PI3K activation. [Display omitted] •Enhanced SIRT6 hinders stemness of human cancer cells with PI3K activation•Enhanced SIRT6 rearranges metabolism of cancer cells with PI3K activation•Enhanced SIRT6 reduces grade and progression of murine tumors with PI3K activation•Anti-cancer-stemness action is independent of SIRT6 histone deacetylase activity Ioris et al. provide in vitro and in vivo evidence that enhanced SIRT6 suppresses cancer progression and stemness in the context of constitutively active PI3K signaling. This effect is, at least in part, through suppression of the PI3K pathway at the transcriptional level and independent of SIRT6’s histone deacetylase activity.